2023
DOI: 10.3847/1538-4357/acd54a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quenching of Galaxies at Cosmic Noon

Abstract: The existence of massive quiescent galaxies at high redshift seems to require rapid quenching, but it is unclear whether all quiescent galaxies have gone through this phase and what physical mechanisms are involved. To study rapid quenching, we use rest-frame colors to select 12 young quiescent galaxies at z ∼ 1.5. From spectral energy distribution fitting, we find that they all experienced intense starbursts prior to rapid quenching. We confirm this with deep Magellan/FIRE spectroscopic observations for a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…Crucially, on the basis of colours alone, this (mini-)quenched galaxy would have been identified as ‘star forming’ by the colour selection criteria 23 , even if including the extension to fast-quenched galaxies 24 . Indeed, its rest-frame U – V colour of 0.16 ± 0.03 mag places it outside the quiescent region of the U V J diagram, regardless of V – J colour 25 , as it is the case for other quiescent galaxies at high redshift 7 . However, thanks to JWST/NIRSpec, we can place stringent upper limits on the nebular emission-line fluxes.…”
Section: Mainmentioning
confidence: 84%
“…Crucially, on the basis of colours alone, this (mini-)quenched galaxy would have been identified as ‘star forming’ by the colour selection criteria 23 , even if including the extension to fast-quenched galaxies 24 . Indeed, its rest-frame U – V colour of 0.16 ± 0.03 mag places it outside the quiescent region of the U V J diagram, regardless of V – J colour 25 , as it is the case for other quiescent galaxies at high redshift 7 . However, thanks to JWST/NIRSpec, we can place stringent upper limits on the nebular emission-line fluxes.…”
Section: Mainmentioning
confidence: 84%
“…However, when rederiving the rest-frame colors using the spectroscopic redshifts, two of the primary targets (HM3-107590 and HM4-55878) shift just outside the quiescent box. Given their location, though, we expect these galaxies to be post-starburst or young quiescent galaxies (e.g., Whitaker et al 2012;Belli et al 2019;Suess et al 2021;Park et al 2023) and thus still have quiescent populations. We will further assess their star formation properties in the next section.…”
Section: Galaxy Sample and Success Ratementioning
confidence: 99%
“…The first direct detection of Balmer and metal absorption lines took nearly 30 hr with GNIRS (Gemini-South) on one galaxy, and the lines were still only marginally detected (e.g., Kriek et al 2009;van Dokkum et al 2009). With the advent of more efficient near-IR spectrographs such as X-Shooter (VLT; Vernet et al 2011), KMOS (VLT; Sharples et al 2013), and MOSFIRE (Keck Observatory;McLean et al 2012), spectroscopic redshifts, robust velocity dispersion measurements, and dynamical mass estimates became available for substantial samples or stacks of distant quiescent galaxies (e.g., van de Sande et al 2011Bezanson et al 2013;Belli et al 2014Belli et al , 2017bLonoce et al 2015;Mendel et al 2015;Onodera et al 2015;Saracco et al 2019;Carnall et al 2022;Park et al 2023;Zhuang et al 2023). In recent years, spectroscopic studies have pushed to even higher redshifts (z > 3; e.g., Glazebrook et al 2017;Schreiber et al 2018;Tanaka et al 2019;Forrest et al 2020;Esdaile et al 2021;Antwi-Danso et al 2023;Carnall et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we investigate galaxies with C Q > 0.49 (defined as quiescent by Belli et al 2019) and t 50 > 30 Myr, indicated by solid black and dotted blue lines, respectively, in the UVJ diagram shown in the left and center panels of Figure 1. This extension to the traditional quiescent box has been proven to capture rapidly quenched and post-starburst galaxies (e.g., Park et al 2023).…”
Section: Sample Selectionmentioning
confidence: 99%